Heavy metal carcinogenicity: a scoping review of observational & experimental evidence - Bailey, Julian; McFarlane, Shelly; Amarakoon, Icolyn (Frontiers in Oncology, 2025)
Environmental heavy metal pollutants are highly toxic and are usually of human origin. Studies have suggested a link between cadmium and arsenic carcinogenesis and geographical location. This review was conducted to explore the methodologies that have been used to determine the risk of carcinogenesis as it relates to cadmium & arsenic exposure as well as geographical location. A search of pertinent literature published up to December 2024 was conducted using the databases, PubMed, and EBSCO. The following MeSH terms were used primarily to search the databases, “heavy metals,” “cadmium,” “arsenic,” “carcinogenesis,” “malignancy,” and “toxicity.” Articles were removed if they were not closely related to the review topic. As evidenced in this review, there has been several research done over the years exploring the heavy metal exposure and the risk for carcinogenesis. The methodologies used to determine this risk are quite uniformed across the various studies. However, there is a paucity of studies dealing with the potential influence of geographical location in relation to the risk of carcinogenesis. This gap in knowledge shows that more work needs to be done to improve on the current knowledge of arsenic and cadmium and carcinogenesis.